Effect of a Liner Material on the Formation of the Wrapping ExplosivelyFormed Penetrator - Xu, Q.Z.; Yin, J.P.; Wang, Z.J.; Yi, J.Y.; Dong, F.D. (Проблемы прочности, 2018)
The wrapping explosively-formed penetrator is a new approach to shape change based on a pre-folded double liner: outer liner of higher density forming the shell and the inner liner of lower density forming the core. The penetrator can not only penetrate the armor but can form lots of fragments behind the target when it attacks light armored objects. The fragments generated by the lateral enhanced effect are able to destroy crew and equipment improving the integrated damage outcome. The shape and materials of the core and shell are the main factors controlling the penetrability and formation of fragments. The effect of liner materials on penetration was studied. with AUTODYN analysis. The results show that the difference in the through-thickness velocities and the interface of the two liners are the main factors leading to the separation of the core and shell. Penetrator with an evident lateral enhanced effect could be helpful to choose appropriate liner materials. The feasibility of forming the penetrator with double liners is substantiated providing a reference for the selection of liner material.